Using of method of replacement of input variables in microprogram finite-state machine with datapath of transitions - Babakov, Roman (Technology audit and production reserves, 2017)
The object of research is a microprogram finite-state machine with datapath of transitions. In its structure, the input signals are fed to the input of the block that forms the codes for the transition operations. A large number of inputs of this unit does not allow to realize it in the basis of memory blocks. The only available basis is the basis of LUT elements of FPGA or similar. To reduce the number of LUT elements used by the circuit of FSM, it is proposed to use the known method of replacement of input variables. Its application leads to the fact that an additional block is added into the structure of the FSM, which converts the input signals of the FSM into special intermediate signals, the number of which is much less than the number of input signals. This leads to a decrease in the input signals of the block that forms the codes of the transition operations, and makes it possible to synthesize it in the basis of the memory blocks without the use of LUT elements. An additional unit that converts input signals into intermediate ones can be synthesized in the basis of multiplexers, which are standard functional blocks of modern FPGAs. This makes it possible to use a smaller number of LUT elements in the structure of the FSM with replacement of input variables than in the prototype structure. Saved in this way LUT elements can be used to implement other units of the FSM or elements of projected computing system. The proposed approach contributes to the saving of hardware amount in the logical circuit of the microprogram finite-state machine with datapath of transitions. This makes this structure more preferable in comparison with the prototype structure from the point of view of hardware amount affecting the final cost of the control unit and the computing system as a whole.